Incentives to lose revisited: The NHL and its tournament incentives - Helena Fornwagner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
This paper analyzes data from a tournament, namely the National Hockey League regular scheduled season of games, which provides incentives to increase effort in order to reach the playoffs and incentives to decrease effort once a team has been eliminated from playoff considerations because of the entry draft. Our results show that teams indeed react to these dual incentives - they win more games when there is still a chance to reach the playoffs and lose more after being eliminated from playoff considerations. One can argue that losing more games after having no more chance to reach the playoffs could be the result of lower motivation or disappointment. This is the first study to show that this is not the only explanation for a higher amount of lost games. Instead, we find that there is a concrete strategy behind losing.
Keywords: C93; D03; L83; M52; 330; tournaments; dual incentives; National Hockey League; losing strategy